1982
DOI: 10.1002/hlca.19820650122
|View full text |Cite
|
Sign up to set email alerts
|

[2 + 2]‐Cycloadditions to Strained Bridgehead Olefins. II. Diphenylketene

Abstract: SummaryThe strained bridgehead olefins bicyclo [3.3. llnon-1-ene (l), bicyclo [4.2. Ilnon-1 (8)-ene (2), and bicyclo [4.2. llnon-1-ene (3), and the comparable monocyclic (E)-1-methylcyclooctene (4) react with diphenylketene (6) to give a single cycloadduct 7, 8, 9 and 10, respectively, in which the diphenyl-substituted C-atom is bound to the bridgehead. The structure of the cyclobutanone 8 has been determined by X-ray analysis of a twin crystal obtained by crystallization with spontaneous enrichment of enantio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This was explained in terms of a concerted "x2a + T2a" transition state. 123 The reactions with l,l-dichloro-2,2-difluoroethylene were accounted for in the usual fashion, i.e., as proceeding via diradicals. On the basis of the product distribution, it was concluded that biradicals 248 and 249 are of similar stability.…”
Section: Bf' 235mentioning
confidence: 99%
“…This was explained in terms of a concerted "x2a + T2a" transition state. 123 The reactions with l,l-dichloro-2,2-difluoroethylene were accounted for in the usual fashion, i.e., as proceeding via diradicals. On the basis of the product distribution, it was concluded that biradicals 248 and 249 are of similar stability.…”
Section: Bf' 235mentioning
confidence: 99%
“…21 12 and 14 also gave facile concerted [2 + 2] cycloaddition reactions with a ketene. 22 The twisted double bonds of trans-cycloalkenes (n = 7−10, n is the number of ring atoms) exhibit higher reactivity compared to their unstrained cis-analogues. 21 In these examples, the reactivity of the twisted double bond mimics that of a twisted alkene (cf.…”
mentioning
confidence: 99%